Working together : succeeding in a multicultural organization - Simons, George F. (Crisp Pub. Menlo ParkUS, 1994)
Seeks to promote mutual understanding and respect between persons of different cultures in the workplace. Explains how to reverse prejudicial thinking; how to speak and listen effectively to persons from different backgrounds. Demonstrates how gestures and body language differ among cultures. Also addresses issues such as sexual orientation, and people with disabilities.